2023
DOI: 10.1097/prs.0000000000010604
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Cartilage Microtissue Regenerated by Autologous Chondrocytes for Nasal Augmentation: A 5-Year Follow-Up Study

Abstract: Background: A lack of ideal filling materials is a critical limitation in current rhinoplasty. Cartilage sheet regeneration by autologous chondrocytes is expected to provide an ideal source of material. However, the inability to perform minimally invasive transplantation of cartilage sheets has greatly limited the clinical application of this material. In this article, the authors propose the concept of injectable cartilage microtissue (ICM) based on cartilage sheet technology, with the aim of achieving minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…W e want to applaud the authors for introducing a relatively novel concept of "injectable cartilage microtissue" (ICM) as a new strategy for minimally invasive augmentation rhinoplasty. 1 The authors have previously demonstrated the ability to successfully generate cartilage sheets, but they were unsuitable for minimally invasive rhinoplasty. 2 Traditional materials for augmentation rhinoplasty, such as autologous implants and artificial prostheses, have limitations such as donor-site morbidity and foreign body reactions.…”
mentioning
confidence: 99%
“…W e want to applaud the authors for introducing a relatively novel concept of "injectable cartilage microtissue" (ICM) as a new strategy for minimally invasive augmentation rhinoplasty. 1 The authors have previously demonstrated the ability to successfully generate cartilage sheets, but they were unsuitable for minimally invasive rhinoplasty. 2 Traditional materials for augmentation rhinoplasty, such as autologous implants and artificial prostheses, have limitations such as donor-site morbidity and foreign body reactions.…”
mentioning
confidence: 99%